Designing interfaces in public settings - Reeves, Stuart (2009)
The rapidly increasing reach of computation into our everyday public settings presents new and significant challenges for the design of interfaces. One key feature of these settings is the increased presence of third parties to interaction, watching or passing-by as conduct with an interface takes place.